Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1177/0960327111405863
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine concentrations changes in the PTU-induced hypothyroid rat brain and the ameliorating role of folic acid

Abstract: Thyroid hormones are recognized as the key metabolic hormones that play a critical role in the development of central nervous system (CNS) throughout life. The present study was designed to determine the changes in brain monoamine concentrations in 6-n-propyl thiouracil (PTU)-induced hypothyroid rats, in addition to the ameliorating role of folic acid treatment. Fifty male albino rats were equally divided into five groups; first and second groups were the control and folic acid groups, respectively, while the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
35
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 37 publications
3
35
0
Order By: Relevance
“…They regulate synaptic transmission (15), modulate the synthesis and turnover of neurotransmitters and modify the sensitivity of their receptors (42,51). They modulate signal transduction pathways in the CNS through Ca 2+ channels.…”
mentioning
confidence: 99%
“…They regulate synaptic transmission (15), modulate the synthesis and turnover of neurotransmitters and modify the sensitivity of their receptors (42,51). They modulate signal transduction pathways in the CNS through Ca 2+ channels.…”
mentioning
confidence: 99%
“…Hypothyroidism has been reported to cause mild hyperhomocysteinaemia (increased homocysteine concentration in the blood) [4][5][6][7][8]. The mechanism by which hypothyroidism causes mild hyperhomocysteinaemia is not clear but altered remethylation is likely to be involved.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, complex changes in folic acid metabolism occur in thyroid dysfunction with increases in tetrahydrofolate and decreases in methyltetrahydrofolate in hypothyroid rat liver [9]. Alteration in thyroid hormone level is also known to modulate functions of several tissues in adult animals by modulating their antioxidant defenses [4][5][6][7][8][10][11][12][13]. Overt Thyroid dysfunctions are frequently associated with abnormalities of biochemical liver tests and in severe forms with histologically evident hepatocellular damage the activity of hepatic lipase is decreased [14].…”
Section: Introductionmentioning
confidence: 99%
“…The existence of sustained epigenetic mechanisms of gene regulation in neurons has been implicated in the regulation of complex behavior, including abnormalities in mental disorders (eg, autism and ADHD) (Colvis CM 2005;Tsankova N 2007). Recently, Tousson et al (Tousson E 2011) demonstrated that coadministration of folate ameliorated monoamine concentration changes in a PTUtreated model. Since folate participates in the enzymatic demethylation of histones, this micronutrient could play a role in the epigenetic control of gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…In addition specific neuronal loss, the activation and/or proliferation of astrocytes per se might indirectly contribute to changes in hippocampal TR signaling. Thyroid hormones are known to modulate a number of neurotransmitter systems, including monoamines (Ahmed OM 2010;Tousson E 2011). Genetic studies imply that variants of both dopamine and serotonin systems may frequently occur in ADHD for neurotransmitter uptake, synthesis, and breakdown functions.…”
Section: Introductionmentioning
confidence: 99%